Economic and food security of the Russian Federation in the context of global challenges ("Journal "U". Economy. Management. Finance.", 2025)
This article examines such concepts as: economic security, food security, project financing in agriculture. The main forms of project financing are discussed. Statistics on such indicators as GDP, inflation rate, budget deficit in the country, the number of agricultural organizations and the index of agricultural production are also provided.
Keywords: economic security; food security; GDP; inflation rate; budget deficit in the country; number of agricultural organizations and index of agricultural production